Long-term analysis of carbonaceous fractions of particulate at a Central Mediterranean site in Italy - Eva Merico; Daniela Cesari; Adelaide Dinoi; Serena Potì; Antonio Pennetta; Ermelinda Bloise; Daniele Contini (Atmospheric Pollution Research, 2025)

Spatial and seasonal variability of the contribution of sources to PM2.5, PM10 and their oxidative potential in different sites in a central Mediterranean area - Serena Potì; Eva Merico; Marianna Conte; Florin Unga; Daniela Cesari; Adelaide Dinoi; Anna Rita De Bartolomeo; Antonio Pennetta; Ermelinda Bloise; Giuseppe Deluca; Giuseppe Egidio De Benedetto; Roberto Ferrera; et al. (Science of The Total Environment, 2025)

Pollution sources affecting the oxidative potential of fine aerosols in a Portuguese urban-industrial area - an exploratory study - Nuno Canha; Sara Gonçalves; Diogo Sousa; Carla Gamelas; Sergio Mendez; Sandra Cabo Verde; Susana Marta Almeida; Anna Rita de Bartolomeo; Maria Rachele Guascito; Eva Merico; Daniele Contini (Air Quality, Atmosphere & Health, 2024)
This study targets to determine the oxidative potential (OP) of fine aerosols in an urban-industrial area of the Lisbon Metropolitan Area (Portugal) and, in addition, to identify which pollution sources may have an impact on the OP levels of fine aerosols. For this purpose, thirty samples were selected from a set of 128 samples collected over one year (Dec 2019-Nov 2020), based on the highest load for each source (both mass and %) previously assessed by source apportionment studies (using Positive Matrix Factorisation, a total of 7 different sources were identified: soil, secondary sulphate, fuel-oil combustion, sea, vehicle non-exhaust, vehicle exhaust and industry). The OP associated with the water-soluble components of PM 2.5 was assessed using the dithiothreitol (DTT) method. The samples had a mean DTT activity (normalised to the mass) of 12.9 ± 6.6 pmol min − 1 µg − 1 , ranging from 3.5 to 31.8 pmol min − 1 µg − 1 . The DTT activity (normalised to the volume, $${\text{O}\text{P}}_{\text{V}}^{\text{D}\text{T}\text{T}}$$ ) showed to have a significant positive association with PM 2.5 levels (R 2 = 0.714). Considering that the mass contributions of the different sources to the PM 2.5 levels were known, Spearman correlations were assessed and significant correlations were found between $${\text{O}\text{P}}_{\text{V}}^{\text{D}\text{T}\text{T}}$$ and three different sources: vehicle exhaust (ρ = 0.647, p -value = 0.001), fuel-oil combustion (ρ = 0.523, p -value = 0.012) and industry (ρ = 0.463, p -value = 0.018). Using a multiple linear regression analysis, these three sources were found to explain 82% of the variability in $${\text{O}\text{P}}_{\text{V}}^{\text{D}\text{T}\text{T}}$$ , with vehicle exhaust being the most influential source.

Characterisation of the correlations between oxidative potential and in vitro biological effects of PM10 at three sites in the central Mediterranean - Maria Rachele Guascito; Maria Giulia Lionetto; Franco Mazzotta; Marianna Conte; Maria Elena Giordano; Roberto Caricato; Anna Rita De Bartolomeo; Adelaide Dinoi; Daniela Cesari; Eva Merico; Laura Mazzotta; Daniele Contini (Journal of Hazardous Materials, 2023)

Concentration and size distribution of atmospheric particles in southern Italy during COVID-19 lockdown period - Marianna Conte; Adelaide Dinoi; Fabio Massimo Grasso; Eva Merico; Maria Rachele Guascito; Daniele Contini (Atmospheric Environment, 2023)

Inter-comparison of carbon content in PM10 and PM2.5 measured with two thermo-optical protocols on samples collected in a Mediterranean site - Eva Merico; Daniela Cesari; Adelaide Dinoi; Andrea Gambaro; Elena Barbaro; Maria R. Guascito; Lorena C. Giannossa; Annarosa Mangone; Daniele Contini (Environmental Science and Pollution Research, 2019)

Contribution of harbour activities and ship traffic to PM2.5, particle number concentrations and PAHs in a port city of the Mediterranean Sea (Italy) - Antonio Donateo; Elena Gregoris; Andrea Gambaro; Eva Merico; Roberto Giua; Alessandra Nocioni; Daniele Contini (Environmental Science and Pollution Research, 2014)